Evaluation of Bile Salt Hydrolases, Cholesterol-Lowering Capabilities, and Probiotic Potential of Enterococcus faecium Isolated From Rhizosphere - Singhal, Neelja; Maurya, Anay Kumar; Mohanty, Shilpa; Kumar, Manish; Virdi, Jugsharan Singh (Frontiers in Microbiology, 2019)
Bile salt hydrolase (BSH) activity, hypo-cholesterolemic effect and probiotic properties have been reported for Enterococcus strains isolated from animal- and human-gut and, fermented foods but not for strains isolated from environmental niches, like aquatic and terrestrial plants, soil and water. The present study is the first report on isolation of Enterococcus faecium from rhizospheric soils which harbor bsh gene, remove cholesterol in-vitro and possess essential and desirable probiotic attributes. Fifteen samples were collected from different sites located in northern, southern and central regions of India, of which five yielded pure colonies which were named as LR2, LR3, ER5, LR13 and VB1. These were identified by 16S rRNA gene sequencing as E. faecium and evaluated for BSH activity, cholesterol-lowering potential in-vitro and probiotic properties. Our results indicated that all the strains were capable of surviving in harsh conditions of gastro-intestinal tract and did not harbor any of the virulence genes. Though, all strains showed the presence of bsh and potential for cholesterol removal, E. faecium strain LR13 showed a remarkable cholesterol removal capability, vancomycin susceptibility and possessed most of the desirable and essential attributes of a probiotic. Hence, it seems to be fairly promising probiotic candidate which needs to be further evaluated in in vivo studies, especially for hypo-cholesterolemic potential.